Determinants of load capacity factor in an emerging economy: The role of green energy consumption and technological innovation - Liu, Xuan; Olanrewaju, Victoria Olushola; Agyekum, Ephraim Bonah; El-Naggar, Mohamed F.; Alrashed, Mohammed M.; Kamel, Salah (Frontiers in Environmental Science, 2022)
Brazil’s ability to provide safe and dependable resources that can assist the nation achieve its goal of becoming carbon neutral by 2060 will have a significant impact on the nation’s sustainable development. Therefore, this study performs ARDL and frequency domain causality tests to evaluate the effect of disintegrated energy, technological innovation and economic growth on load capacity factor in South Africa between 1990 and 2018. The ARDL bounds test affirms a long-run interrelationship between the selected indicators in South Africa. The long-run elasticities show that economic expansion and nonrenewable energy deteriorate ecological quality, while green energy and technological innovation significantly boost ecological quality. The results of the frequency causality show that in the long-term, renewable energy, economic growth, technological innovation and nonrenewable energy Granger cause load capacity factor suggesting that the regressors can forecast the environmental quality in South Africa. Overall, these results demonstrate the significance of renewable energy in the fight against ecological deterioration. According to the aforementioned findings, South Africa’s environmental damage may be greatly reduced by renewable energy.